Association between Asymptomatic Bacteriuria and Pre-Eclampsia - Rezavand, Negin; Veisi, Firooze; Zangane, Mrayam; Amini, Roghaye; Almasi, Afshin (Global journal of health science, 2015)
Asymptomatic bacteriuria is one of the most common and important bacterial infections during pregnancy and can result in progressive infections and endanger maternal as well as fetal health. In this study, we assessed the relationship between asymptomatic bacteriuria and pre-eclampsia. In this case-control study, pregnant women who presented to Imam Reza Hospital in Kermanshah in 2013-14 were studied. The minimum sample size was calculated as 125 pregnant women in each group with a total of 250 subjects. There were 125 women with pre-eclampsia and 125 women without pre-eclampsia (control group). Matching was done for age, gestational age, and parity between case and control groups. Matching was verified by a P value of 0.061 for maternal age and gestational age and 0.77 for parity. The statistical analyses were done by applying the chi-squared test and determining odds ratio (OR) for having bacteriuria in univariate logistic regression as well as multivariate regression with adjusting the effect of maternal age, gestational age, and parity. Pyuria and bacteriuria were significantly more common in pre-eclampsia group than in control group. The results showed that a significant association existed between asymptomatic bacteriuria and pre-eclampsia. The rate of asymptomatic bacteriuria was 6.8 times higher in women with pre-eclampsia compared to those without pre-eclampsia. Further studies are required for better clarification of association between asymptomatic bacteriuria and pre-eclampsia.